The Effect of Organizational Culture and Worklife Balance on Employee Performance through Job Satisfaction - Galih` Evendi; Hary Sulaksono; Diana Dwi Astuti (Innovation Business Management and Accounting Journal, 2025)
This study aims to examine and analyze the influence of organizational culture and worklife balance on employee performance through job satisfaction among third-party employees at the Bank Indonesia Malang Representative Office. The research development is conducted by testing and analyzing both the direct influence of organizational culture and worklife balance on employee performance and their indirect influence through job satisfaction. This study is a quantitative research, employing a saturated sampling technique. The respondents consist of 74 third-party employees at the Bank Indonesia Malang Representative Office. The study utilizes multivariate data analysis techniques, as it analyzes more than one variable, using the Structural Equation Modeling (SEM) method with the WarpPLS 7.0 application. Overall, the research findings indicate that organizational culture and work-life balance have a positive and significant impact on both employee performance and job satisfaction, while job satisfaction also has a positive and significant impact on employee performance. As a result, employee performance becomes more productive and contributes positively to the institution's success and reputation.